Macroprudential policy in the euro area: does cross country and banking heterogeneity matters? - Maria, Bruno Alexandre de Sousa Santa (2021)
The following Dissertation addresses how cross country and banking heterogeneity affects the design and implementation of a given macroprudential policy framework in the Euro Area. Panel data econometric methods to quarterly data collected from 12 Euro Area Member States, from 2015 up to 2019, from the BIS, ECB, and Eurostat databases were employed. The extracted variables are related to credit lent to the non-financial sector (households and nonfinancial firms) and their corresponding main drivers, according to the literature related to financial stability topics. It was explored the effects of bank’s capital indicators, following the criteria established from the Basel III accords, namely liquidity, leverage, credit risk, bank’s average size, interest rate charged to non-financial economic agents, real estate asset prices, monetary aggregates and business cycle on bank lending dynamics. Furthermore, robustness checks and the possible nonlinear effects of the explanatory variables described previously were also tested. The findings state that different factors influence credit dynamics on households and nonfinancial firms, reflecting that possible measures that have the main goal of controlling excessive credit growth must be well-targeted, in order to avoid general approaches. Moreover, the existence of non-linear effects on the variables statistically significant to explain credit flows was observed, showing that a future macroprudential policy framework for the Euro Area must consider cross country and banking heterogeneity among Member States.